2005
DOI: 10.1177/8756087905053791
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vinyl Acetate Content and Polyisobutylene Concentration on the Properties of Metallocene Polyethylene-Ethyl Vinyl Acetate Coextruded Film for Stretch and Cling Film Applications

Abstract: A range of EVA-mLLDPE-EVA coextruded films, with polyisobutylene (PIB) masterbatch content of 0-20% and vinyl acetate (VA) comonomer content of 6, 12, and 18%, is manufactured. The films are aged at 45 C for up to 28 days to enable tack (cling) development. The results show that film tack strength improves significantly with aging. Increased VA concentration in the surface layer also shows significant improvement in film tack strength. The film tensile strength, elongation, and tear properties in both machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…McNally and Small investigated the effect of extrusion processing parameters as well as polyisobutylene concentration on the properties of polyethylene stretch and cling films, using a blown film and cast a film‐extrusion system and storage conditions of 25, 35, and 45°C for up to 28 days. Although McNally and Small have used with the T‐Peel test a different test method to study the cling behavior, the observed increase of the cling force with increasing aging time is in good accordance with the results presented here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…McNally and Small investigated the effect of extrusion processing parameters as well as polyisobutylene concentration on the properties of polyethylene stretch and cling films, using a blown film and cast a film‐extrusion system and storage conditions of 25, 35, and 45°C for up to 28 days. Although McNally and Small have used with the T‐Peel test a different test method to study the cling behavior, the observed increase of the cling force with increasing aging time is in good accordance with the results presented here.…”
Section: Resultsmentioning
confidence: 99%
“…Cling forces increase with aging time at 25°C, showing significantly higher cling strengths if stored at higher temperatures up to 45°C. In both cases a maximum of the cling force could be expected after approximately two weeks of aging . Conditioning the stretch film at −40°C results in steady cling forces.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The low molecular weight (low viscosity or high MFI) resin will go to the surface of the film in this case. It has also been reported that, in incompatible blends, chains with higher surface free energy or having polar groups have a preference to be located at the film surface (Jalbert et al, 1993;Lee and Archer, 2001;Chen and Gardella ,1994;McNally, 2005a;McNally, 2005b). This higher concentration of EVA at the film surfaces causes superior hot-tack and seal strength results for high EVA content films.…”
Section: Blend Morphologymentioning
confidence: 87%